Avaliação do estresse oxidativo induzido por superfícies de titânio - Queiroz, Jana Dara Freires de (2011)
Commercially pure Titanium (cp Ti) is a material largely used in orthopedic and dental implants due to its biocompatibility properties. Changes in the surface of cp Ti can determine the functional response of the cells such as facilitating implant fixation and stabilization, and increased roughness of the surface has been shown to improve adhesion and cellular proliferation. Various surface modification methods have been developed to increase roughness, such as mechanical, chemical, electrochemical and plasma treatment. An argon plasma treatment generates a surface that has good mechanical proprieties without chemical composition modification. Besides the topography, biological responses to the implant contribute significantly to its success. Oxidative stress induced by the biomaterials is considered one of the major causes of implant failure. For this reason the oxidative potential of titanium surfaces subjected to plasma treatment was evaluated on this work. CHO-k1 cells were cultivated on smooth or roughed Ti disks, and after three days, the redox balance was investigated measuring reactive oxygen species (ROS) generation, total antioxidant capacity and biomarkers of ROS attack. The results showed cells grown on titanium surfaces are subjected to intracellular oxidative stress due to hydrogen peroxide generation. Titanium discs subjected to the plasma treatment induced less oxidative stress than the untreated ones, which resulted in improved cellular ability. Our data suggest that plasma treated titanium may be a more biocompatible biomaterial.